2011
DOI: 10.1111/j.1741-3737.2011.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Headed Toward Equality? Housework Change in Comparative Perspective

Abstract: This paper examined gendered housework in the larger context of comparative social change, asking specifically whether cross-national differences in domestic labor patterns converge over time. Our analysis of data from 13 countries (N =11,065) from the 1994 and 2002 International Social Survey Program (ISSP), confirmed that social context matters in shaping couples’ division of labor at home, but also showed that context affects patterns of change. Our results suggested that, compared to the most egalitarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 48 publications
3
84
0
2
Order By: Relevance
“…An interesting distinction is also evident in the different pace of change between these countries and others in which the gender division of housework has been more equal across the period. This distinction is in line with the findings of Geist and Cohen (2011), whose analysis of International Social Survey Program data between 1994 and 2002 showed that more traditional countries move faster towards egalitarianism in routine housework over time.…”
Section: Resultssupporting
confidence: 71%
“…An interesting distinction is also evident in the different pace of change between these countries and others in which the gender division of housework has been more equal across the period. This distinction is in line with the findings of Geist and Cohen (2011), whose analysis of International Social Survey Program data between 1994 and 2002 showed that more traditional countries move faster towards egalitarianism in routine housework over time.…”
Section: Resultssupporting
confidence: 71%
“…Prior efforts to understand this puzzle have focused on the "stalled revolution" in the domestic division of labor (Hochschild and Machung [1989] 2003; see also Bianchi et al 2012;Geist and Cohen 2011); the uneven or incomplete adoption of effective anti-discrimination, diversity, and family-friendly personnel policies (e.g., Dobbin, Kim, and Kalev 2011;Hirsh 2009;Kelly 2010;Williams, Blair-Loy, and Berdahl 2013); deep-rooted cultural beliefs about gender differences in competencies that affect labor supply and demand in high-paying occupations and that often become embodied in organizations (e.g., Acker 1990; Ridgeway 2011); and persistent gender segregation in the workplace (e.g., Charles and Grusky 2004;Weeden and Sørensen 2004).…”
mentioning
confidence: 99%
“…Si bien se ha documentado la reducción de la diferencia en el tiempo dedicado al mismo entre hombres y mujeres, ellas continúan realizando la mayor parte del trabajo no remunerado, aun cuando ha aumentado su participación en el trabajo extradoméstico (Pedrero, 2005;Sayer, 2010;Geist y Cohen, 2011). Justamente esta tendencia ha puesto en duda la llamada hipótesis de la especialización, es decir, que la división sexual del trabajo obedece fundamentalmente a la decisión de los miembros de las parejas a especializarse en un ámbito u otro para maximizar sus recursos y capacidades (Becker, 1981).…”
Section: Trabajo Doméstico En Las Parejas De Doble Ingresounclassified